POLA PEMBINAAN PENDIDIK DAN TENAGA KEPENDIDIKAN PENDIDIKAN NONFORMAL - Kusmiadi, Ade (JIV-Jurnal Ilmiah Visi, 2006)
Three factors determining the success of nonformal education are organization, human resources, and relevancy of programs to the needs of society. The programs has its own target, that is human resources of nonformal education personnel. Among them are supervisors, facilitator, and other personnel served by the Directorate. On the other hand, their roles balance the needs of the General Directorate and Quality Improvement Eduational Teachers as well as the society. Therefore, it’s necesary for them to improve their knowledge and skills continously. In return, the productivity ot the organization of nonformal education is to be improved simultanneosly. There should be trainings for them to improve their knowledge and skills as well as to be professional. The success of trainigs is proven through their skill knowledge improvement in the work place.